University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 2 - Section 2.2 - Limit of a Function and Limit Laws - Exercises: 29

Answer

$\lim\limits_{x \to -2}\frac{(-2x-4)}{(x^{3}+2x^{2})} = -0.5=\frac{-1}{2}$

Work Step by Step

Simplify: $\frac{(-2x-4)}{(x^{3}+2x^{2})}= -\frac{2(x+2)}{x^{2}(x+2)} = -\frac{2}{x^{2}}$ $\lim\limits_{x \to -2}\frac{(-2x-4)}{(x^{3}+2x^{2})}= \lim\limits_{x \to -2}-\frac{2}{x^{2}} = -\frac{2}{4} = -\frac{1}{2} = -0.5$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.